2014
DOI: 10.4196/kjpp.2014.18.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of a Selective Endothelin ETAReceptor Antagonist in Rat Model of L-Methionine-induced Vascular Dementia

Abstract: The present study was designed to investigate the efficacy of selective ETA receptor antagonist, ambrisentan on hyperhomocysteinemia-induced experimental vascular dementia. L-methionine was administered for 8 weeks to induce hyperhomocysteinemia and associated vascular dementia in male rats. Ambrisentan was administered to L-methionine-treated effect rats for 4 weeks (starting from 5th to 8th week of L-methionine treatment). On 52nd day onward, the animals were exposed to the Morris water maze (MWM) for testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Chronic L‐methionine administration is well reported to produce HHcy‐induced VCID [40]. Endothelial dysfunction, impairment of learning and memory, and neuropathological changes have been reported to be associated with HHcy [36,57]. HHcy is further known to cause severe oxidative stress and decrease antioxidant enzyme activities and produce deleterious effects on endothelial cells causing endothelial cell damage [58,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic L‐methionine administration is well reported to produce HHcy‐induced VCID [40]. Endothelial dysfunction, impairment of learning and memory, and neuropathological changes have been reported to be associated with HHcy [36,57]. HHcy is further known to cause severe oxidative stress and decrease antioxidant enzyme activities and produce deleterious effects on endothelial cells causing endothelial cell damage [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…L‐methionine (1.7 g/kg/day, p.o.) was administered for 56 days (8 weeks) to produce HHcy‐induced vascular dementia in rats [36]. Rats were subjected to Morris water maze (MWM) test from 52 nd till 56 th day to assess learning and memory.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, a nanobody was constructed that may be useful as a potential new ET B antagonist in the treatment of melanoma [214]. Further studies suggested beneficial effects of ERA treatment on cognitive function in experimental models of vascular dementia [215,216]. The therapeutic potential of ERAs in vascular dementia or in Alzheimer disease has not yet been studied in humans yet, but preclinical and pathology data offer hope.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it also attenuates the hyperhomocysteinemia, β-amyloid and renovascular hypertension-induced vascular dementia in rats. Further, the administration of selective endothelin ET-A receptor antagonist i.e., ambrisentan attenuates the L-methionine-induced vascular dementia in rats [46]. ECEs inhibitors can control the accumulation of ET-1 peptide and activation of ET receptors.…”
Section: Endothelin-converting Enzymementioning
confidence: 94%